Individuals with Peripheral Artery Disease (PAD) and Type 1 Diabetes Are More Likely to Undergo Limb Amputation than Those with PAD and Type 2 Diabetes - Jain, Nidhi (J Clin Med, 2020)
Background: Limited data exist comparing how type 1 diabetes mellitus (DM) and type 2 DM may have differential effects on peripheral artery disease (PAD) severity. We aimed to study the association of type of DM with the procedure utilized in hospitalizations with a diagnosis of PAD. Methods: We used the national inpatient sample databases from 2003 to 2014 to identify hospitalizations with a diagnosis of PAD and type 1 or type 2 DM. Logistic regression was utilized to evaluate the association between type of DM and procedure utilized (amputation-overall, major, endovascular revascularization, surgical revascularization). Results: We identified 14,012,860 hospitalizations with PAD diagnosis and DM, 5.6% (n = 784,720) had type 1 DM. The patients with type 1 DM were more likely to present with chronic limb-threatening ischemia (CLTI) (45.2% vs. 32.0%), ulcer (25.9% vs. 17.7%), or complicated ulcer (16.6% vs. 10.5%) (all p < 0.001) when compared to those with type 2 DM. Type 1 DM was independently and significantly associated with more amputation procedures (adjusted odds ratio = 1.12, 95% confidence interval [CI] I 1.08 to 1.16, p < 0.001). Overall, in-hospital mortality did not differ between the individuals with type 1 and type 2 DM. The overall mean (95% CI) length of stay (in days) was 6.6 (6.5 to 6.6) and was significantly higher for type 1 DM (7.8 [7.7 to 8.0]) when compared to those with type 2 DM (6.5 [6.4 to 6.6]). Conclusion: We observed that individuals with PAD and type 1 DM were more likely to present with CLTI and ulcer and undergo amputation when compared to those with PAD and type 2 diabetes. Further studies are needed to better understand the underlying mechanisms behind these findings and to identify novel interventions to reduce the risk of amputation in patients with type 1 DM.